2014
DOI: 10.1364/josab.31.000332
|View full text |Cite
|
Sign up to set email alerts
|

Nonreciprocal electromagnetic wave propagation in one-dimensional ternary magnetized plasma photonic crystals

Abstract: In this paper, we propose a one-dimensional ternary photonic crystal based on magnetized plasma to obtain nonreciprocal propagation. By employing the transfer matrix method, the transmission spectra of the counterpropagating plane waves incident from air upon either end of the periodic structure are calculated. Our results reveal that there is a significant contrast between the transmittance of the waves propagated in opposite directions. This means that the structure shows nonreciprocal effects. It is shown t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Based on the results in the published works, [8][9][10][11] PBGs and defect modes of 1D and 2D PPCs not only can be significantly tuned by their topology parameters but also can be easily manipulated by the parameters of plasma since the physical characteristics of plasma can be adjusted by many external factors, 6 such as the temperature of electron, the plasma density, and the external magnetic field. Therefore, some microwave devices can be realized based on the 1D, 2D, or 3D PPCs, such as filter, 12 omnidirectional reflector, 13 isolator, 14 waveguide, 7 and optical switching. 15 It is worth to be noticed that the plasma is a kind of dispersive materials and the propagating modes through the plasma can be tuned by the external magnetic field.…”
mentioning
confidence: 99%
“…Based on the results in the published works, [8][9][10][11] PBGs and defect modes of 1D and 2D PPCs not only can be significantly tuned by their topology parameters but also can be easily manipulated by the parameters of plasma since the physical characteristics of plasma can be adjusted by many external factors, 6 such as the temperature of electron, the plasma density, and the external magnetic field. Therefore, some microwave devices can be realized based on the 1D, 2D, or 3D PPCs, such as filter, 12 omnidirectional reflector, 13 isolator, 14 waveguide, 7 and optical switching. 15 It is worth to be noticed that the plasma is a kind of dispersive materials and the propagating modes through the plasma can be tuned by the external magnetic field.…”
mentioning
confidence: 99%
“…PPC experiments have also been conducted by many researchers, where it has been shown that plasma demonstrates metamaterial properties under specific conditions [17]. Consequently, PPCs have some abnormal properties in some cases [18][19][20], such as magneto-optical effects, nonlinearity and nonreciprocal properties.…”
Section: Introductionmentioning
confidence: 99%
“…are orthogonal unit vectors. Obviously, in reciprocal space, the dielectric distribution can also be expanded as[17][18][19] In equation(4), η(G) is the Fourier transform. Obviously, equation (2) can be expressed as[17][18][19] …”
mentioning
confidence: 99%
“…Various peculiar physical characteristics of PPCs also were investigated, such as the magneto-optical effects, 21 the nonlinearity 22 and the nonreciprocal properties. 23 In those works, the enhancements of the PBGs is one of important topics, since larger PBGs are more valuable for the devices.…”
Section: Introductionmentioning
confidence: 99%